Anti-tumor alkaloids from Peganum harmala. (May 2022) - Zhang, Qin; Zan, Yan-Hui; Yang, Han-Gao; Yang, Meng-Yue; Liu, Fang-Shen; Li, Sheng-Ge; Peng, Xiao-Hui; Lin, Bin; Li, Zhan-Lin; Li, Da-Hong; Hua, Hui-Ming
Abstract: Six alkaloids peharmalines F–K, along with 14 known ones, were isolated from the aerial part of Peganum harmala L.. The structures of the isolated compounds were determined based on their HR-ESI-MS data, extensive NMR spectroscopic analyses, and ECD calculations. 3-(4-Hydroxyphenyl)quinoline exhibited potent antiproliferative activity against the HepG-2 cell lines with an IC50 value of 3.05 μM. Norharmane displayed a moderate inhibition against A549 and HepG-2 cells with IC50 values of 16.45 μM and 17.27 μM, respectively. Graphical abstract: Image 1 Highlights: Six unreported alkaloids were isolated from the aerial parts of Peganum harmala. Peharmaline F possesses a rare quinoline-vasicine hybrid skeleton. 3-(4-Hydroxyphenyl)quinoline showed potent inhibition against hepatoma HepG-2 cells.